TANGGAPAN CUSTOMER TERHADAP KUALITAS PELAYANAN DAN KEPUASAN J&T EXPRESS CABANG CIKEMBAR - Agung Gumelar Apit Supardi; M. Tegar Ramdani (PT Naureen Digital Education, 2023)
The purpose of this study is to see companies that provide quality services and satisfaction, which can meet the level of customer interest, will be able to survive more because they create superior value than their competitors. One of the service industries that can apply this is the logistics service industry or the delivery of goods. The data collection method was carried out through descriptive qualitative research, in which an informant who was invited for an interview was expected to be able to produce an in-depth description of observable speech, writing, and/or behavior of an individual, group, community, or organization that was studied from the point of view of whole, comprehensive and holistic. Data analysis was performed with a percentage score from the ideal. The results of the study show that the customer is very satisfied with the J&T Express delivery service for the Cikembar Branch. This is in line with the statements of 40 respondents who answered with an average score of 77.50% and 81.42%, with good prices that are lower than competitors or from other delivery services. Price also causes high customer satisfaction on easy payment indicators, namely, by COD, transfers, paying on the spot, and credit for relationships.